DESIGNING VOCABULARY SCRAPBOOK USING CANVA FOR ELEMENTARY SCHOOL - Kayyis, Rahmatika; Yuniarti, Fatma; Imaniar, Milu Arumi (Premise: Journal of English Education and Applied Linguistics, 2023)
The research aims to design a vocabulary scrapbook using Canva and determine whether the product is feasible and practical to teach vocabulary to elementary students. The type of research is R&D by Borg and Gall (2003). This research was conducted at SDN 1 Rejosari. The data collection instruments used were the Questionnaire, interview, and observation analyzed using qualitative and quantitative analysis. The results of media feasibility based on the assessment of media and material experts are categorized as excellent criteria, and the results of teacher and student responses after the tryout and implementation of the product. The media has been successfully designed and effectively used to support teaching vocabulary to elementary. This study also implies that Canva has contributed to the term, function, and benefit of creating the media for teaching English. A teacher is not only using Canva as the online media for teaching, but it can be a supplement to create a lot of media creation that supports the teaching and learning process offline in the classroom. It also gives insight into scrapbooks and other media that can be designed and developed using Canva.